Ohmic transition at contacts key to maximizing fill factor and performance of organic solar cells - Jun-Kai Tan (Nature Portfolio, 2018)
The importance of ohmic contacts for organic solar cells has been recognized, but how the transition to ohmic behavior occurs is unknown. Tan et al. show that this transition happens separately beyond Fermi-level pinning, when the interfacial contact resistivity becomes sufficiently low.